PENGEMBANGAN E-MODUL TEKS CERPEN BERBASIS KONTEKSTUAL MENGGUNAKAN APLIKASI ANY FLIP SISWA KELAS XI SMA NEGERI 4 TANJUNGPINANG TAHUN AJARAN 2023/2024: PENGEMBANGAN E-MODUL TEKS CERPEN BERBASIS KONTEKSTUAL MENGGUNAKAN APLIKASI ANY FLIP SISWA KELAS XI SMA NEGERI 4 TANJUNGPINANG TAHUN AJARAN 2023/2024 - Siska Hastuti; Harry Andheska; Legi Elfitra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Based on these problems, it can be understood that innovation is needed regarding the important role of teaching materials in the form of e-modules to support learning activities in the classroom. The use of teaching materials can attract interest and arouse students' learning motivation. Not only the use of teaching materials, the learning approach can also be expected to be able to help teachers to handle students in their learning and students will be helped to better understand what is being conveyed by the teacher. The best learning approach to use is a contextual-based approach. The contextual approach is a learning approach that begins by taking, simulating, telling, having a dialogue, asking questions or discussing the daily life experienced by students, then bringing it into the concept that will be studied and discussed. Based on the validation results from media experts, it was declared